Evaluating the effect of viral posts on social media engagement - Emanuele Sangiorgio; Niccolò Di Marco; Gabriele Etta; Matteo Cinelli; Roy Cerqueti; Walter Quattrociocchi (Scientific Reports)
Abstract As virality has become increasingly central in shaping information sources’ strategies, it raises concerns about its consequences for society, particularly when referring to the impact of viral news on the public discourse. Nonetheless, there has been little consideration of whether these viral events genuinely boost the attention received by the source. To address this gap, we analyze content timelines from over 1000 European news outlets from 2018 to 2023 on Facebook and YouTube, employing a Bayesian structural time series model to evaluate the impact of viral posts. Our results show that most viral events do not significantly increase engagement and rarely lead to sustained growth. We identify two primary types of viral effects corresponding to different mechanisms of collective attention response. A ‘loaded-type’ virality manifests after a sustained growth phase, representing its final burst, followed by a decline in attention. A ‘sudden-type’ virality, with news emerging unexpectedly, reactivates the collective response process. Moreover, quick viral effects fade faster, while slower processes lead to more persistent growth. These findings highlight the transient nature of viral events and underscore the importance of consistent, steady attention-building strategies to establish a solid connection with the user base rather than relying on sudden visibility spikes.